FGD ON MSME MANAGEMENT STRATEGIES IN FACING GLOBAL COMPETITION FROM AN ISLAMIC PERSPECTIVE - Bulutoding, Lince; Sari, Nur Rahmah; Suhartono, Suhartono; Jannah, Raodahtul; Sumarlin, Sumarlin; Syariati, Namla Elfa; Iwang, Baso; Sirajuddin, Sirajuddin; Lutfi, Mufti; Habibi, Ahmad; Zainal, Ghaliah Jalwaa Insyrah; Saifullah, Fu’ad; Iffah, Nur; Masrawati, Masrawati (JICS : Journal Of International Community Service, 2024)
Tapandullu Beach, located in Mamuju Regency, is a stunning tourist destination, renowned for its outstanding natural beauty. With its fine white sand and crystal clear waters, the beach is an ideal choice for visitors seeking a tranquil and relaxing nature experience. Around the beach, a number of MSME players are trying to capitalize on the existing tourism potential. They offer a variety of specialty products, ranging from local food to handicrafts that reflect regional culture. These businesses not only add value for visitors, but also contribute to the economic growth of the local community. However, challenges cannot be ignored. MSME players must compete with products from outside that often have better variety and quality. This study examines the management strategies of Micro, Small and Medium Enterprises (MSMEs) in facing global competition, with a sharia-based approach. Sharia Enterprise Theory (SET) is used to understand the sharia-based approach. The method used is Focus Group Discussion (FGD) involving MSME players in Tapandullu Beach, Mamuju Regency. The results showed that the application of sharia principles not only increases the competitiveness of MSMEs in a sustainable manner, but also helps in maintaining ethical values and social responsibility. MSMEs and managers have three groups of stakeholders that must be taken into account in every accountability. FGD participants identified key challenges such as limited capital, poor marketing, and product quality. Proposed solutions included access to Islamic financing, digital cooperation, and skills training. The findings are expected to guide other MSME players in formulating suitable strategies, so that they can improve their position and contribution in the global market more effectively.